Why Does Infant Stepping Disappear and Can It Be Stimulated by Optic Flow?. Issue 2 (8th October 2014) - Barbu‐Roth, Marianne; Anderson, David I.; Streeter, Ryan J.; Combrouze, Marie; Park, Juana; Schultz, Brooke; Campos, Joseph J.; Goffinet, François; Provasi, Joëlle
Abstract : Two independent experiments ( n  = 22 and n  = 22) showed that 2‐month‐old infants displayed significantly more stepping movements when supported upright in the air than when supported with their feet contacting a surface. Air‐ and surface‐stepping kinematics were quite similar (Experiment 2). In addition, when data were collapsed across both experiments, more air steps and more donkey kicks were seen when infants were exposed to optic flows that specified backward compared to forward translation. The findings challenge the currently accepted heavy legs explanation for the disappearance of stepping at 2 months of age and raise new questions about the visual control of stepping.